NGS-based identification of druggable alterations and signaling pathways – hepatocellular carcinoma case report - Kotelnikova, E.A.; Logacheva, M.D.; Nabieva, E.R.; Pyatnitskiy, M.A.; Vinogradov, D.V.; Makarova, A.S.; Demin, A.V.; Paleeva, A.G.; Kremenetskaya, O.S.; Penin, A.A.; Klepikova, A.V.; Kasianov, A.S.; et al. (Вiopolymers and Cell, 2015)
Aim. To identify potential cancer driving or clinically relevant molecular events for a patient with hepatocellular carcinoma. Methods. In order to achieve this goal, we performed RNA-seq and exome sequencing for the tumor tissue and its matched control. We annotated the alterations found using several publicly available databases and bioinformatics tools. Results. We identified several differentially expressed genes linked to the classical sorafenib treatment as well as additional pathways potentially druggable by therapies studied in clinical trials (Erlotinib, Lapatinib and Temsirolimus). Several germline mutations, found in XRCC1, TP53 and DPYD, according to the data from other clinical trials, could be related to the increased sensitivity to platinum therapies and reduced sensitivity to 5-Fluorouracil. We also identified several potentially driving mutations that could not be currently linked to therapies, like deletion in CIRBP, SNVs in BTG1, ERBB3, TCF7L2 et al. Conclusions. The presented study shows the potential usefulness of the integrated approach to the NGS data analysis, including the analysis of germline mutations and transcriptome in addition to the cancer panel or the exome sequencing data. Мета. Ідентифікувати потенційно онкодрайверні або клінічно значущі молекулярні події у пацієнта з гепатоклітинною карциномою. Методи. РНК- та екзомне секвенування пухлинної тканини та відповідного контролю. Анотування знайдених змін, використовуючи декілька загальнодоступних баз даних та біоінформатичних програм. Ми також порівняли транскрипційний профіль досліджуваної пухлини з транскриптомами клітинних ліній з бази даних Genomics of Drug Sensitivity in Cancer. Результати. Ідентифіковано кілька генів, що дифференційно експресуються, і пов’язані як з класичною терапією сорафенібом, так і з додатковими сигнальними шляхами, що потенційно вразливі до терапії препаратами, які досліджувались у клініческих випробуваннях (ерлотініб, лапатініб та темсіролімус). Декілька гермінативних мутацій, знайдених в XRCC1, TP53 та DPYD, згідно з даними інших клінічних випробувань, можуть бути пов’язані з підвищеною чутливістю до платинових терапій та зменшеною чутливістю до 5-фторурацилу. Ми також ідентифікували декілька потенційно драйверних мутацій, які на цей час не можуть бути пов’язані з терапіями, наприклад делеції у CIRBP, заміни в BTG1, ERBB3, TCF7L2 тощо. Висновки. Запропоноване дослідження демонструє потенційну корисність інтегрованого підходу до NGS аналізу даних, в тому числі аналізу гермінативних мутацій та транскриптому у додаток до використання онкологічних генних панелей або даних секвенування екзому. Цель. Выявлении ключевых или клинически значимых молекулярных событий для пациента с гепатоцеллюлярной карциномой. Методы. РНК- и экзомное секвенирования опухолевой и нормальной ткани. Мы проаннотировали найденные генетические нарушения, используя несколько общедоступных баз данных и биоинформатических инструментов. Результаты. Мы определили несколько дифференциально экспрессированных генов, связанных с классической схемой лечения препаратом сорафениб, а также дополнительные пути потенциально поддающиеся терапии препаратами, включенными в клинические испытания (Эрлотиниб, Лапатиниб и Темсиролимус). Несколько герминативных мутаций, найденных в XRCC1, TP53 и DPYD, по данным из других клинических испытаний, могут быть связаны с повышенной чувствительностью к препаратам платины и пониженной чувствительностью к 5-фторурацилу. Мы также определили несколько потенциально драйверных мутаций в генах CIRBP, замены в BTG1, ErbB3, TCF7L2 и др., которые в настоящее время не связаны с терапией. Выводы. Данное исследование показывает потенциальную значимость комплексного подхода к анализу данных NGS, в том числе анализа герминативных мутаций и транскриптома в дополнение к данным из генных панелей или секвенирования экзома.